The Effect of Artichoke Against the Toxicity of Oxfendazole, a Promising Agent for the Treatment and Control of Helminth Infections - Yilmaz, Seval; Kaya, Emre (My University, 2025)
This study was carried out to determine the protective and/or therapeutic roles of artichoke against oxidative stress that oxfendazole (OX) can cause in rats. No intervention was made in the first group. Artichoke extract was applied to the second group at dose of 1.5 g/kg/day for seven days by gavage, to the third group for 15 days at 100 mg/kg/day dose an OX by gavage. The fourth group was formed as Artichoke+OX and the fifth group was OX+Artichoke. In the fourth group, artichoke treatment was started seven days before the OX application and continued for seven days, followed by 15 days after OX application. In the fifth group, artichoke and OX applications were started simultaneously. Upon completion of investigation, levels of malondialdehyde (MDA), reduced glutathione (GSH), and activities of antioxidant enzymes, including catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were assessed in blood tissue. In comparison to control group, the group treated with OX exhibited significantly elevated levels of MDA (p<0.001) and GSH (p<0.001), alongside reduced activities of CAT (p?0.001), GSH-Px (p<0.01), and SOD (p<0.001). While the values in all parameters in the fifth group approached the control group values, MDA levels in the fourth group could not reach the control group values. In addition, there was no statistical difference in CAT and GSH-Px activities between the OX-administered group and fourth group. As a result, considering the doses and durations applied in our study against oxidative stress caused by OX, it was observed that therapeutic effect of artichoke was stronger than its protective effect.
Keywords: Antioxidant; oxidative stress; artichoke; Oxfendazole